Development of live attenuated fowl adenovirus isolate of Malaysia for vaccine production - Mohamed Sohaimi, Norfitriah (2017)
Fowl adenovirus (FAdV) infection is one of the major threats among viral diseases in poultry industry worldwide. The disease caused severe economic losses due to high mortality and poor production. Malaysian`s FAdV isolate are highly pathogenic in chickens and has been identified as primary pathogen of inclusion body hepatitis (IBH) and gizzard erosion. It is indeed an urgent need to develop FAdV vaccines to prevent and control FAdV infection. It was objective of the study to develop live attenuated FAdV isolate of Malaysia for future production of vaccine against the disease. FAdV isolate (UPM1137) was obtained from liver sample of chickens during outbreak of IBH and gizzard erosion. The isolate was successfully isolated and identified in specific pathogen free (SPF) embryonated chicken eggs and Vero cells. Thickening and cloudy of chorioallantoic membrane (CAM) with pale, petechial haemorrhages and multifocal area of necrosis of the liver and hydropericardium of embryo were recorded at day 9 post-inoculation (pi). The cytopathic effect (CPE) in Vero cells revealed cytoplasmic extensions and formation of plaque at day 6pi. It was confirmed that the isolate belong to FAdV by PCR with expected PCR size product and through sequence analysis. Partial hexon gene region with 1166 base pair (bp) of nucleotide (nt) sequence from SPF embryos and Vero cells samples were assigned with Genbank accession number, KF866370 (UPM1137E2) and KF866371 (UPM1137V1), respectively. For fiber gene, 1094bp of nucleotide sequence were deposited into GenBank with accession number KY305950 (UPM1137E2) and KY364903 (UPM1137V1). The isolate is highly related to group E species under serotype 8b. The isolate is highly pathogenic in SPF embryonated chicken eggs with 100% mortality and typical gross and histological lesions associated with FAdV. The embryonic mortality pattern was delayed from 17th consecutive passages (E17) to E20. This is consistent with the molecular changes in both L1 loop and knob regions of the nucleotide bases and amino acid in hexon and fiber gene and may indicate virus attenuation. Molecular changes were also prominent at 5th consecutive passages of the virus in Vero cells (V5). However, the FAdV isolate was highly susceptible to be adapted and attenuated in primary chicken embryo liver (CEL) cells. Early CPE was observed at 2nd consecutive passages (CEL2) to CEL19 within 24 to 48 hours post inoculation (pi) in the form of cells rounding, refractile and clumping. The CPE formation was delayed from CEL20 to CEL35 within 48 to 72 hours pi. Nucleotide sequences of hexon and fiber gene from all propagated isolates were deposited to GenBank and assigned with the accession numbers KY305943 to KY305949 (hexon) and KY305951 to KY305957 (fiber). Molecular changes in L1 loop of hexon gene are minimal in nucleotide bases of CEL5 to CEL20 without caused any amino acid changes. All changes mainly occur in other part of hexon gene. However, changes noticeable from CEL25 to CEL35 propagated FAdV isolates. Sequence analysis in fiber gene revealed both nucleotide and amino acid changes in knob region are prominent at high passage level from CEL20 to CEL35. It was demonstrated that the marker gene for adaptation in CEL cells and SPF embryonated chicken eggs were identified in nucleotide of L1 loop hexon gene at position 90(T-C) and in knob of fiber gene at both nucleotide and amino acid at position 1078(G-C) and 360(A-P), respectively. Additionally, the marker gene for attenuation in CEL cells was detected in knob region of fiber gene at position 1062(A-C). Sequence analysis of hexon and fiber gene product of all the samples either from the SPF eggs, Vero cells or CEL cells passages revealed 1166bp and 1094bp, respectively belongs to FAdV group E serotype 8b. Phylogenetic tree constructions revealed that isolates were clustered and closed to each other. The pathogenicity, immunogenicity and efficacy of an attenuated FAdV isolate CEL35 (106.7TCID50/ml) was determined in 1-day-old SPF chickens via oral (0.1ml) and subcutaneous (SQ) (0.1ml) route of inoculation. On day 14 post-inoculation (pi), chickens in challenged groups were inoculated with 0.2ml pathogenic FAdV isolate, UPM11134 (108.3TCID50/ml) via intraperitoneal (IP) route. The study shown that the attenuated FAdV isolate is non-pathogenic and safe in SPF chickens without exhibit clinical signs associated with FAdV infection throughout the trial. The FAdV inoculated chickens in challenged group were normal without exhibit abnormal clinical signs, gross and histological lesions. However, chickens in non-inoculated group showed clinical signs of weakness, depression and recumbency at day 4 post-challenge (pc) prior recovery on day 8pc. The body weight was significantly lower (p<0.05) and the liver was pale at 14 day pc as compared to non-challenged group. FAdV antibody titer was not detected in control group throughout the trial. In group of chicken inoculated via SQ route, the antibody titer was 648 ± 188 and 324 ± 85 at day 14 and 28pi, respectively. The antibody titer in chicken inoculated via oral route was 316 ± 118 and 163 ± 17 at day 14 and 28pi, respectively, was not significantly difference (p>0.05) when compared to the SQ and control groups. In challenged groups, the antibody titer was significantly increased (p<0.05) mainly in control (6276 ± 1983) and oral (5496 ± 1688) groups with exception in SQ (3895 ± 1858) group at day 14pc. It was demonstrated that attenuated FAdV is safe, non-pathogenic, immunogenic and able to protect chickens from FAdV infection. The subcutaneous is an effective route of inoculation as compared to oral route. The pathogenicity and immunogenicity of FAdV attenuated in CEL cells, CEL35 (106.7TCID50/ml), and in SPF embryonated chicken eggs, E20 (108.7TCID50/ml) were determined in 1-day-old commercial broiler chickens via oral (0.5ml) or intraperitoneal (IP) (0.5ml) route. The study revealed that the attenuated isolates were non-pathogenic in commercial broiler chickens. Neither clinical signs nor gross and histological lesions in the liver was recorded in all groups of chicken throughout 21 days trial. The mean body weight of chickens was significantly low (p<0.05) in inoculated groups as compared to control group at days 7 and 14pi in both routes of inoculation. At day 21pi, body weight in inoculated chickens was significantly high (p<0.05) as compared to control group. The FAdV antibody titer was high in day old chicks due to presence of maternal derived antibody (MDA) and was significantly declined (p<0.05) from day 0 (7795 ± 1414) to day 21pi (69 ± 34). The FAdV inoculated chickens using CEL35 attenuated isolate revealed oral (3985 ± 776) and IP (3734 ± 809) route had identical pattern of antibody titer and were not significant difference (p>0.05) between route of inoculation throughout the trial. Similarly, in chickens inoculated with E20 FAdV, the antibody titer in oral (4119 ± 792) and IP (4598 ± 871) group were equally distributed among the routes. There were no differences in antibody titer between attenuated isolates either through oral or IP routes (p>0.05). However, FAdV inoculated chickens with CEL35 (2348 ± 1800) and E20 (1833 ± 792) attenuated isolates via IP route have high antibody titer significantly (p<0.05) compared to control group (69 ± 34) at day 21pi. It was concluded that the attenuated FAdV isolate are non-pathogenic and immunogenic in commercial broiler chickens. The attenuated FAdV isolate in CEL cells and SPF embryonated chicken eggs induced similar antibody response either through oral or IP routes. It was concluded that FAdV is highly susceptible in SPF embryonated chicken eggs and primary CEL cells rather than in Vero cells with nucleotide and amino acid changes in hexon at L1 loop region and in fiber gene at knob region. The attenuated isolates are non-pathogenic in SPF and commercial broiler chickens with capability to induce FAdV antibody. It appears that parenteral route is an effective route of FAdV inoculation when compared to the oral route and the attenuated isolates are suitable to be used for future development of FAdV vaccine against the disease.